2014
DOI: 10.1016/j.eswa.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Discrete techniques applied to low-energy mobile human activity recognition. A new approach

Abstract: Human activity recognition systems are currently implemented by hundreds of applications and, in recent years, several technology manufacturers have introduced new wearable devices for this purpose. Battery consumption constitutes a critical point in these systems since most are provided with a rechargeable battery. In this paper, by using discrete techniques based on the Ameva algorithm, an innovative approach for human activity recognition systems on mobile devices is presented. Furthermore, unlike other sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…However, the majority of existing solutions detect only a few activities. A major step forward would be the possibility for the system to recognize additional activities after the initial training [33,34].…”
Section: Activity Recognition Systems For Eldersmentioning
confidence: 99%
“…However, the majority of existing solutions detect only a few activities. A major step forward would be the possibility for the system to recognize additional activities after the initial training [33,34].…”
Section: Activity Recognition Systems For Eldersmentioning
confidence: 99%
“…Physical activity recognition can be done in a number of ways which usually consists of a battery powered wireless sensor node, measuring accelerometer data [5]. This paper focuses on obtaining accelerometer from a smartphone, other current research has shown interest in this and it has shown promising results and successful implementation [1]- [3], [5], [6].…”
Section: Activity Recognition Through Analysis Of Related Workmentioning
confidence: 99%
“…This paper focuses on obtaining accelerometer from a smartphone, other current research has shown interest in this and it has shown promising results and successful implementation [1]- [3], [5], [6]. Activity recognition is not a new concept and has been implemented for some time.…”
Section: Activity Recognition Through Analysis Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity recognition (de la Concepción et al, 2014;Fernández-Caballero et al, 2012) has aroused a great interest in the past decade and has been addressed by many research groups using different kinds of physical devices and reasoning techniques. The great interest in activity recognition can be explained in many ways.…”
Section: Introductionmentioning
confidence: 99%